2009
DOI: 10.1007/s10508-009-9523-5
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Tracking of Men’s Preferences for Waist-to-Hip Ratio and Breast Size of Women

Abstract: Studies of human physical traits and mate preferences often use questionnaires asking participants to rate the attractiveness of images. Female waist-to-hip ratio (WHR), breast size, and facial appearance have all been implicated in assessments by men of female attractiveness. However, very little is known about how men make fine-grained visual assessments of such images. We used eye-tracking techniques to measure the numbers of visual fixations, dwell times, and initial fixations made by men who viewed front-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(147 citation statements)
references
References 37 publications
10
135
2
Order By: Relevance
“…Specifically, women's attractiveness ratings were negatively associated with WHR, which is consistent with previous research (Dixson, Dixson, Li, & Anderson, 2007;Dixson et al, 2011;Furnham, Tan, & McManus, 1997;Platek & Singh, 2010 Thus, the weak relationship between women's viewing time for female pictures and sexual attractiveness ratings here may indicate that heterosexual women's viewing times for female pictures is not strongly related to the perceived attractiveness of female pictures.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, women's attractiveness ratings were negatively associated with WHR, which is consistent with previous research (Dixson, Dixson, Li, & Anderson, 2007;Dixson et al, 2011;Furnham, Tan, & McManus, 1997;Platek & Singh, 2010 Thus, the weak relationship between women's viewing time for female pictures and sexual attractiveness ratings here may indicate that heterosexual women's viewing times for female pictures is not strongly related to the perceived attractiveness of female pictures.…”
Section: Discussionsupporting
confidence: 90%
“…A finding that a low WHR ratio is preferred, and that individuals focus on reproductively relevant regions, would further support the possibility that cognitive strategies are used to assess the physical characteristics that are sought for in women, primarily by male participants. Therefore, in this study, we hypothesized the following: (1) as has been shown by Dixson et al (2010Dixson et al ( , 2011b, Singh (1993), Singh and Young (1995), and Suschinsky et al (2007), the areas of the breast and midriff will receive more visual attention than other areas; (2) the lower the WHR, the more attractive ratings it will receive; and (3) there will be gender differences in the amount of visual attention displayed, that is, men will spend longer time viewing the images than will women. …”
Section: Present Studymentioning
confidence: 98%
“…Besides the WHR, breast size also plays an important role in the evaluation of attractiveness. In an eye-tracking study, Dixson et al found that men's initial visual fixation is either on the breasts or the waist, not on the face or lower body-at least when a naked woman is shown [20]. In a similar study conducted by Hewig et al, in which participants were presented with pictures of dressed women and men, the male participants' initial look was at the face of women, followed by fixation on the breasts [21].…”
Section: Sex and Attractionmentioning
confidence: 99%